Treatment of Chronic Experimental Autoimmune Encephalomyelitis with Epigallocatechin-3-Gallate and Glatiramer Acetate Alters Expression of Heme-Oxygenase-1 - Janssen, Antonia (PLoS One, 2015)
We previously demonstrated that epigallocatechin-3-gallate (EGCG) synergizes with the immunomodulatory agent glatiramer acetate (GA) in eliciting anti-inflammatory and neuroprotective effects in the relapsing-remitting EAE model. Thus, we hypothesized that mice with chronic EAE may also benefit from this combination therapy. We first assessed how a treatment with a single dose of GA together with daily application of EGCG may modulate EAE. Although single therapies with a suboptimal dose of GA or EGCG led to disease amelioration and reduced CNS inflammation, the combination therapy had no effects. While EGCG appeared to preserve axons and myelin, the single GA dose did not improve axonal damage or demyelination. Interestingly, the neuroprotective effect of EGCG was abolished when GA was applied in combination. To elucidate how a single dose of GA may interfere with EGCG, we focused on the anti-inflammatory, iron chelating and anti-oxidant properties of EGCG. Surprisingly, we observed that while EGCG induced a downregulation of the gene expression of heme oxygenase-1 (HO-1) in affected CNS areas, the combined therapy of GA+EGCG seems to promote an increased HO-1 expression. These data suggest that upregulation of HO-1 may contribute to diminish the neuroprotective benefits of EGCG alone in this EAE model. Altogether, our data indicate that neuroprotection by EGCG in chronic EAE may involve regulation of oxidative processes, including downmodulation of HO-1. Further investigation of the re-dox balance in chronic neuroinflammation and in particular functional studies on HO-1 are warranted to understand its role in disease progression.